(3EOGQI GdehGQO GdHTQjIs - (3NVjQ cGXe(B, (3MehOs; (3jGSjf(B, (3cGSH GdNQTIs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B,s, 2007)
(3EOGQI GdehGQO GdHTQjI GdESJQGJjLjGJ hGdJMOjGJ,JNWjW GdehGQO GdHTQjI,JOab GdYed hJUeje GdhXGFa hJMdjdgG,GSJbWGH GdehGQO GdHTQjI,JOQjH GdYGedjf,Jbjje COGA GdYGedjf,CfXeI GdCLhQ hGdQhGJH hGdJYhjVGJ,GdYdGbGJ GdUfGYjI hGdfbGHGJ,EOGQI GdSdGeI GdegfjI hGdUMjI,fXe eYdheGJ GdehGQO GdHTQjIs
(3HHdjhZQGajG(B:(3U(B.263-265 (3cTGa GdeUWdMGJ(B:(3U(B.267-276s
Keywords: (3EOGQI GdGaQGOs